Triptan-Induced Torsades de Pointes and Ventricular Fibrillation Cardiac Arrest: Case Report and Review of the Literature - E. Hill, Stanley; La, Kirsten (Current Drug Safety, 2014)
Migraine is a potentially debilitating neurologic disorder affecting approximately 12% of the United States population. Sumatriptan manufacturer-provided drug information states that life threatening arrhythmias, including ventricular tachycardia and ventricular fibrillation (VF), have been reported. A literature search revealed only seven reported cases of ventricular arrhythmias immediately after sumatriptan administration. Twenty minutes after a 42 year old female received sumatriptan, her femoral pulses were not palpable and the electrocardiograph (EKG) showed torsades de pointes followed by VF. After defibrillation and one round of cardiopulmonary resuscitation (CPR), the patient regained spontaneous circulation. The patient was eventually discharged home. Despite studies concluding that sumatriptan has minimal effects on coronary arteries, several cases of sumatriptan-associated myocardial infarction have been documented. In addition, a small number of documented cases have reported life threatening arrhythmias and cardiorespiratory arrest after sumatriptan administration.
Keywords: ventricular fibrillation